Pengaruh Literasi Keuangan, Inklusi Keuangan, Gaya Hidup, Dan Financial Technology Terhadap Perilaku Keuangan Pegawai PT. X di SUMUT - Abdillah Arif Nasution; Muhammad Rijal Balatif (Politeknik Ganesha Medan, 2025)
This research aims to analyze the influence of financial literacy, financial inclusion, lifestyle, income and financial technology on the financial behavior of PT X. This research is associative research and the type of data used is quantitative data. The population in this study was 178 people who were employees of PT. X with a sampling technique using purposive sampling. The data analysis techniques used are descriptive statistical analysis and multiple linear regression. The results of this research show that financial literacy, financial inclusion, lifestyle, income and financial technology simultaneously have a significant influence on the financial behavior of PT X. Partially, financial literacy has a positive and insignificant effect on the financial behavior of PT X, financial inclusion has a positive and significant effect on the financial behavior of PT X, lifestyle has a positive and significant effect on the financial behavior of PT X, income has a positive and insignificant effect on the financial behavior of PT X, financial technology has a positive and insignificant effect on the financial behavior of PT X. The most dominant influence on financial behavior is financial inclusion.